84.7k views
5 votes
-7x - 3x + 2 = -8x - 8 ?? Somebody help show me the process!

User Froston
by
5.4k points

1 Answer

6 votes
If you are trying to solve for x:

Gather like terms: ( -7x -3x)
-7x -3x + 2= -8x -8
-10x + 2= -8x -8

Move terms to the other side of the equation:
-10x + 2= -8x -8 Move variables to the left
-10x + 8x + 2= -8 Move constants to the right
-10x + 8x= -8 -2 By moving, you change its value

Collect like terms:
-10x + 8x = -8 -2
-2x = -10 Divide both sides by -2
x = -5

x= -5 Please like if you found this useful!
User Zoowalk
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.